“In situ similis” Culturing of Plant Microbiota: A Novel Simulated Environmental Method Based on Plant Leaf Blades as Nutritional Pads - Nemr, Rahma A.; Khalil, Mohab; Sarhan, Mohamed S.; Abbas, Mohamed; Elsawey, Hend; Youssef, Hanan H.; Hamza, Mervat A.; Morsi, Ahmed T.; El-Tahan, Mahmoud; Fayez, Mohamed; Patz, Sascha; Witzel, Katja; et al. (Frontiers in Microbiology, 2020)
High-throughput cultivation methods are recently developed to accelerate the recovery of microorganisms reluctant for cultivation. They simulate in situ environmental conditions for the isolation of environmental microbiota through the exchange of growth substrates during cultivation. Here, we introduce leaf-based culture media adopting the concept of the plant being the master architect of its microbial community composition. Pre-physical treatments of sunflower plant leaves, by punching, freezing and/or autoclavation, allowed diffusion of electrolytes and other nutrients to configure the leaf surface as a natural pad, i.e. creating an “in situ similis” environment, suitable for the growth of scarcely isolated microbiota. We used surface inoculation and membrane-filtration methods to assess the culturability of endophytic bacteria from sunflower phyllosphere and rhizosphere. Both methods supported excellent CFUs development when compared to standard R2A medium, with special affinity to support better growth of epiphytic and endophytic populations of the phyllosphere, compared with the rhizosphere. 16S rRNA gene analysis of >122 representative isolates indicated the cultivation of a diverse set of microorganisms by application of the new methods. They documented the predominance of >30 species belonging to many genera of Firmicutes, Proteobacteria and Actinobacteria, especially for genera not commonly reported for sunflower, e.g. Rhizobium, Aureimonas, Sphingomonas, Paracoccus, Stenotrophomonas, Pantoea, Kosakonia and Erwinia. The strategy successfully extended diversity and richness in the endophyllosphere compared to the endorhizosphere, while CFUs grown on the standard R2A medium mainly pertain to Firmicutes, especially Bacillus spp. MALDI-TOF MS analysis was applied to cluster the isolates according to their niche and potential functions, where majority of isolates of endorhizosphere were clustered away from those of the endophyllosphere. Isolates identified as Gammaproteobacteria and Alphaproteobacteria were distinguishably sub-clustered, which was in contrast to the heterogeneous isolates of Firmicutes (Bacillus spp.). In conclusion, the leaf in situ similis cultivation is an effective strategy to support future application of culturomics of plant microbiota. This is an effort to access novel isolates more adapted and competitive in their natural environments, especially those subjected to abiotic stresses of heat and drought in the arid/semi-arid zones.